Rickettsia Species in Ticks Removed from Humans in Istanbul, Turkey - GARGILI KELEŞ, AYŞEN (MARY ANN LIEBERT INC, 2012)
A total of 167 ticks collected from humans in Istanbul (Turkey) in 2006 were screened for Rickettsia species, and nested PCRs targeting gltA and ompA rickettsial fragment genes were carried out. Rickettsia monacensis (51), R. aeschlimannii (8), R. conorii subsp. conorii (3), R. helvetica (2), R. raoultii (1), R. africae (1), R. felis (1), and other Rickettsia spp. (2), were detected. To our knowledge, these Rickettsia species (except R. conorii) had never been reported in ticks removed from humans in Turkey. The presence of R. africae also had not been previously described, either in Hyalomma ticks or in any European tick species. In addition, R. aeschlimannii and R. felis had not been found associated with Rhipicephalus bursa specimens. The presence of human pathogenic Rickettsia in ticks removed from humans provides information about the risk of tick-borne rickettsioses in Turkey.
Keywords: Rickettsia species; Turkey; Ticks from humans; SPOTTED-FEVER GROUP; AESCHLIMANNII INFECTION; BORNE RICKETTSIOSES; EMERGING DISEASES; BITE FEVER; AFRICAE; IDENTIFICATION; DIVERSITY; HELVETICA; EUROPE